If cosecA - cotA = q , then show that q2 -1/q2 +1 +cosA=0

We have,      q = cosec A - cot Aq2 = cosec A - cot A2q2 = cosec2A + cot2A - 2 cosec A . cot Aq2 = 1sin2A + cos2Asin2A - 2 cos Asin2Aq2 = 1 + cos2A - 2 cos A sin2Aq2 = 1 - cos A21 - cos2A = 1-cos A1 - cos A1 - cos A1 + cos A = 1 - cos A1 + cos ANow,LHS = q2-1q2+1 + cos A=1 - cos A1 + cos A - 11-cos A1 + cos A + 1 + cos A=1 - cos A - 1 - cos A1 - cos A + 1 + cos A + cos A=-2 cos A2 + cos A= - cos A + cos A=0=RHS

 

  • 30
What are you looking for?